Non-linear equations for IITJEE Mathematics training

(Non-linear) equations involving three or more variables can only be solved in special cases. We shall here consider some of the most useful methods of solution.

Example 1.

Solve the following system of equations:

x+y+z=13 \ldots \ldots \ldots Equation I

x^{2}+y^{2}+z^{2}=65 \ldots \ldots \ldots Equation II

xy=10 \ldots \ldots\ldots Equation III

Solution I:

From II and III, we get (x+y)^{2} + z^{2}=85

Plug in u=x+y; then this equation becomes u^{2}+z^{2}=85.

Also, from I, we get u+z=13

hence, we obtain u=7 \hspace{0.1in}or \hspace{0.1in}u=6, z=6 \hspace{0.1in} or \hspace{0.1in}7.Thus,we have

x+y=7, xy=10; and x+y=6, xy=10. Hence, the solutions are

x=5, \hspace{0.1in} or \hspace{0.1in} 2; y=2, \hspace{0.1in} or \hspace{0.1in} 5; z=6;

or,

x=3 \pm \sqrt{-1}; y=3 \mp \sqrt{-1}; z=7.

Example 2:

Solve the following system of equations:

(x+y)(x+z)=30 Equation I

(y+z)(y+x)=15 Equation II

(z+x)(z+y)=18 Equation III

Solution: 2:

Write u, v, w for y+z, z+x, x+y respectively; thus

vw=30, uw=15, vu=18…..call this equations A

Multiplying these equations together, we have

u^{2}v^{2}w^{2}=30 \times 15 \times 18 = 8100. Hence, uvw=\pm 90.

Combining this result with each of the equations in A, we have

u=3, v=6. w=5; or, u=-3, v=-6, w=-5; therefore, we get two sets of linear equations, as follows:

y+z=3

z+x=6

x+y=5

for which the solution set is: x=4, y=1, z=2; and the other set is:

y+z=-3

z+x=-6

x+y=-5

for which the solution set if x=-4, y=-1, z=-2.

Example 3:

Solve the following system of equations:

y^{2}+yz+z^{2}=49…call this equation (1)

z^{2}+xz+x^{2}=19…call this equation (2)

x^{2}+xy+y^{2}=39…call this equation (3)

Subtracting (2) from (1), we get the following:

y^{2}-x^{2}+z(y-x)=30, that is, (y-x)(x+y+z)=30…call this equation (4).

Similarly, from (1) and (3), we get the following:

(z-x)(x+y+z)=10…call this equation (5).

Hence, from equations (4) and (5), by division, we get the following:

\frac{y-x}{z-x}=3, hence, y=3x-2z

Substituting in Equation (3), we obtain x^{2}-3xz+3z^{2}=13.

From (2), we get the following: x^{2}+xz+z^{2}=19

Solving these homogeneous equations (hint: put z=mx, where m is parameter to be found), we get the following:

x=\pm 2, z=\pm 3; and therefore, y=\pm 5

or, x=\pm \frac{11}{\sqrt{7}}; z=\pm \frac{1}{\sqrt{7}}; and therefore, y=\mp \frac{19}{\sqrt{7}}.

Example 4:

Solve the following system of equations:

x^{2}-yz=a^{2}

y^{2}-zx=b^{2}

z^{2}-xy=c^{2}

Solution 4:

Multiply the equations by y, z, and x respectively, and add; then,

c^{2}x+a^{2}y+b^{2}z=0…call this equation I

Multiply the equations by z, x and y respectively; and add; then

b^{2}x+c^{2}y+a^{2}z=0…call this equation II

From (I) and (II), by cross multiplication,

\frac{x}{a^{4}-b^{2}c^{2}}=\frac{y}{b^{4}-c^{2}a^{2}}=\frac{x}{c^{4}-a^{2}b^{2}}=k, suppose.

Substitute in any one of the given equations; then,

k^{2}(a^{6}+b^{6}+c^{6}-3a^{2}b^{2}c^{2})=1; hence, we get the following solution:

\frac{x}{a^{4}-b^{2}c^{2}}=\frac{y}{b^{4}-c^{2}a^{2}}=\frac{z}{c^{4}-a^{2}b^{2}}=\pm \frac{1}{\sqrt{a^{6}+b^{6}+c^{6}-3a^{2}b^{2}c^{2}}}.

More stuff in the pipeline,

Nalin Pithwa

 

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out / Change )

Twitter picture

You are commenting using your Twitter account. Log Out / Change )

Facebook photo

You are commenting using your Facebook account. Log Out / Change )

Google+ photo

You are commenting using your Google+ account. Log Out / Change )

Connecting to %s

%d bloggers like this: